2022
DOI: 10.1109/jerm.2021.3096172
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Alzheimer's Disease Using RF Signals and Machine Learning

Abstract: Objectives: Alzheimer's disease is one of the most fastest growing and costly diseases in the world today. It affects the livelihood of not just patients, but those who take care of them, including care givers, nurses, and close family members. Current progression monitoring techniques are based on MRI and PET scans which are inconvenient for patients to use. In addition, more intelligent and efficient methods are needed to predict what the current stage of the disease is and strategies on how to slow down its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Accordingly, establishing safety levels by standardizing the frequency, power, and exposure times of microwaves, along with their applications, is of the upmost importance. Some studies have reported that microwaves may affect our CNSs differently, with some indicating that microwaves are involved in the manifestation of CNS diseases [ 108 ], including Alzheimer’s disease [ 109 , 202 , 203 , 204 , 205 , 206 ]. ( Figure 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, establishing safety levels by standardizing the frequency, power, and exposure times of microwaves, along with their applications, is of the upmost importance. Some studies have reported that microwaves may affect our CNSs differently, with some indicating that microwaves are involved in the manifestation of CNS diseases [ 108 ], including Alzheimer’s disease [ 109 , 202 , 203 , 204 , 205 , 206 ]. ( Figure 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…While absolute values for accuracy & precision were available, other metrics like delay, complexity and scalability were evaluated in terms of fuzzy range sets of Low (L), Medium, High (H), and Very High (VH), which were decided based on their internal configurations and performance across different scenarios. Based on this strategy, table 1 showcases parameters for these models, Based on this analysis, it can be observed that DF [43], TPA GAN [4], PCA NET [17], THS GAN [50], SSDP [24], MA Net [30], TSA CNN [26], and RL [42] showcase high accuracy, while DLN [40], Fuzzy GBDT [22], PD Res Net [21], GERF [39], PC SVM [41], SSDP [24], SALL [25], THS GAN [50], ACGA [23], TSA CNN [26], and RL [42] showcase high precision, which makes them useful for a wide variety of real-time clinical use cases.…”
Section: Discussionmentioning
confidence: 99%
“…The authors of this paper outline an automated deep learning-based movie-based PD detection system. Researchers describe a 3D convolutional neural networks (CNN) ability to categorize the severity of PD [26]. The severity of PD may be identified through non-medical transfer learning, according to research, despite the paucity of clinical data in this area.…”
Section: In-depth Review Of Different Models For Identification Of Hu...mentioning
confidence: 99%
See 1 more Smart Citation
“…The authors of [ 58 ] utilized a stepped monopole antenna for its microwave unobtrusive sensing [ 59 ] ability to detect and create image zones of the brain that are affected by Alzheimer’s disease, providing an improvement over PET scans, which rely on biomarkers. The antenna was fabricated using conductive textile material (Shieldex Zell) and flexible substrate material (RS-PRO Viscose Wool Felt) to provide adaptability in the placement of the antenna [ 60 ].…”
Section: Sensor Designmentioning
confidence: 99%